2015
DOI: 10.2147/cia.s91997
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent physical exercise with simultaneous cognitive training to enhance dual-task walking of older adults: a secondary analysis of a 6-month randomized controlled trial with 1-year follow-up

Abstract: BackgroundAbout one-third of people older than 65 years fall at least once a year. Physical exercise has been previously demonstrated to improve gait, enhance physical fitness, and prevent falls. Nonetheless, the addition of cognitive training components may potentially increase these effects, since cognitive impairment is related to gait irregularities and fall risk. We hypothesized that simultaneous cognitive–physical training would lead to greater improvements in dual-task (DT) gait compared to exclusive ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
175
6
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(200 citation statements)
references
References 60 publications
11
175
6
8
Order By: Relevance
“…Results of these studies are heterogeneous. While some of them reported preserved training effects for trained DT performances after 12 weeks [20,24,29], others could not demonstrate retained improvements of trained DT performances after different follow-up periods (4 weeks [28] or 12 months [27]). …”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Results of these studies are heterogeneous. While some of them reported preserved training effects for trained DT performances after 12 weeks [20,24,29], others could not demonstrate retained improvements of trained DT performances after different follow-up periods (4 weeks [28] or 12 months [27]). …”
Section: Introductionmentioning
confidence: 91%
“…Of the few studies that investigated sustainability of trained DTs in people without CI [20,24,[27][28][29], only three studies showed maintained improvements in trained DTs after a follow-up of 3 months [24,29] and 2-3 months [20]. Within the studies that did not find long-term effects, the initial training effects at the end of the intervention were limited, as documented by a p value at the significance level (p = 0.05 [28]) or only moderate effects sizes for training effects (p = 0.011, effect size r = 0.37 [27]). Results of the present study stand out as sustainability of DT training was documented in a study sample with diagnostically confirmed probable dementia.…”
Section: Sustainability Of Effects Sustainability Of Effects On Trainmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of cardiorespiratory fitness, lower extremity strength, balance and reaction time were found to be associated with better gait in several populations, such as community dwelling older adults (Ploutz-Snyder et al 2002;Tiedemann et al 2005;Callisaya et al 2010), patients with multiple sclerosis (Sandroff et al 2013) and stroke survivors (Eng & Tang 2007;Taylor-Piliae et al 2012). Physical exercise has also been found effective to improve gait and walking capacity in multiple populations, such as older adults (Gill et al 2004;Eggenberger et al 2015;Bouaziz et al 2016), stroke survivors (Saunders et al 2016) and people with dementia (Bossers et al 2015;Kemoun et al 2010). Because low physical fitness levels have been demonstrated in people with ID (Lahtinen et al 2007;Hilgenkamp et al 2010), this may also influence their gait.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that individuals aged 65 to 84 years can benefit significantly from aerobic exercise, improving physical function parameters such as muscle mass, balance, and walking speed (Shigematsu et al 2002;Short et al 2003;Harber et al 2009). In addition, a multicomponent exercise including aerobic exercise has been reported to have a positive impact on balance, gait speed, walking distance, and mobility in older adults aged 65 years and over (Eggenberger et al 2015) or aged 79 to 90 years (Rogers et al 2003;Ansai et al 2016). Progressive moderate-to high-intensity group programs including balance, jumping, and lower limb strength exercises can maintain or even improve the physical function of healthy older women aged 65 to 80 years (Korpelainen et al 2006;Karinkanta et al 2010).…”
Section: Introductionmentioning
confidence: 99%